2021
DOI: 10.1007/s00406-021-01334-z
|View full text |Cite
|
Sign up to set email alerts
|

The role of microglia in neuropsychiatric disorders and suicide

Abstract: This narrative review examines the possible role of microglial cells, first, in neuroinflammation and, second, in schizophrenia, depression, and suicide. Recent research on the interactions between microglia, astrocytes and neurons and their involvement in pathophysiological processes of neuropsychiatric disorders is presented. This review focuses on results from postmortem, positron emission tomography (PET) imaging studies, and animal models of schizophrenia and depression. Third, the effects of antipsychoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 235 publications
2
22
0
2
Order By: Relevance
“…The reactivity and density of microglia in brain areas (prefrontal cortex, anterior cingulate cortex, and hippocampus) are increased in patients with depression (Yang et al, 2020;Brisch et al, 2021). Indeed, changes in microglial state have been observed in different models of depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reactivity and density of microglia in brain areas (prefrontal cortex, anterior cingulate cortex, and hippocampus) are increased in patients with depression (Yang et al, 2020;Brisch et al, 2021). Indeed, changes in microglial state have been observed in different models of depression.…”
Section: Discussionmentioning
confidence: 99%
“…Research shows the presence of an increase in IL-6 and TNF-α levels in major depressive disorder (MDD) patients cerebrospinal fluid (CSF), and brain parenchyma, in the context of a possible increased microglial reaction (Enache et al, 2019). Unfortunately, a growing body of evidence from human autopsy found that abnormalities of the microglial states and functions have been observed in the brains of patients who committed suicide after depression (Yang et al, 2020;Brisch et al, 2021). These studies suggest that regulating the microglial state transition seems particularly important in the cause and treatment of depression.…”
Section: Introductionmentioning
confidence: 99%
“…Although 5p was the dominant strand in the adult human cortex, both strands were abundant in this tissue. Within brain tissue, miR-142 expression appeared to be very specific to microglial cells—a cell type that has recently received much attention in BD research [ 108 , 109 ].…”
Section: Discussionmentioning
confidence: 99%
“…SCZ is associated with myelinogenesis defects and white matter damage, and the number of OLs and myelination are significantly reduced in the PFC and hippocampus [ 110 , 111 ]. Microglia are activated, to perform synapsis pruning and phagocytosis of broken neurons, and inhibit the release of neurotrophic factors, to induce the death of gray matter neurons [ 112 ]. The autopsy results of some SCZ patients showed increased astrocytes, which might be associated with neurotransmitter response, synaptic dysfunction, and inflammatory response [ 113 , 114 ].…”
Section: Mechanism Of Rna M6a-modified Glial Cells In the Occurrence ...mentioning
confidence: 99%